The London clearing banks - Nevin, Edward; Davis, Edward W. (London, Elek, 1970)
This book is a systematic and comprehensive study of the emergence and evolution of the institutions now known as the London Clearing Banks, and of their problems and policies in the changing British economy of the 20th century
Includes bibliographical references.
osc 9/10/17
Loans
Keywords: Banks and banking; Finance; Monetary theory